12th International Conference on Conservative Management of Spinal Deformities – SOSORT 2015 Annual Meeting. Issue 1 (August 2016) - Parent, Eric; Richter, Alan; Aulisa, Angelo; Guzzanti, Vincenzo; Pizzetti, Paolo; Poscia, Andrea; Aulisa, Lorenzo; Simony, Ane; Christensen, Steen; Andersen, Mikkel; Negrini, Alessandra; Donzelli, Sabrina; et al.
Abstract O1 The functional properties of paraspinal muscles in adolescents with idiopathic scoliosis (AIS): A systematic review of the literature Eric Parent, Alan Richter O2 The importance of the lateral profile in the treatment of idiopathic scoliosis Angelo Gabriele Aulisa, Vincenzo Guzzanti, Paolo Pizzetti, Andrea Poscia, Lorenzo Aulisa O3 Radiological outcome in Adolescent idiopathic scoliosis patients 20 years after treatment Ane Simony, Steen Bach Christensen, Mikkel O Andersen O4 Junctional Kyphosis, how can we detect and monitor it during growth? Alessandra Negrini, Sabrina Donzelli, Laura Maserati, Fabio Zaina, Jorge H Villafane, Stefano Negrini O5 Usefulness of the clinical measure of trunk imbalance in adolescent idiopathic scoliosis Carole Fortin, Erin Grunstein, Hubert Labelle, Stefan Parent, Debbie Ehrmann Feldman O6 Can ultrasound imaging be used to determine curve flexibility when designing spinal orthoses? Edmond Lou, Rui Zheng, Doug Hill, Andreas Donauer, Melissa Tilburn, Jim Raso O7 Reliability of the Schroth curve type classification in adolescents with idiopathic scoliosis (AIS) Sanja Schreiber, Eric Parent, Greg Kawchuk, Douglas Hedden O8 Can Trunk Appearance Perception Scale (TAPS) be used as a descriptive tool of scoliosis severity? Judith Sánchez-Raya, Antonia Matamalas Adrover, Elisabetta D'Agata, Joan Bagó Granell O9 Magnitude of the Cobb angle on an X-ray in relation to the angle of trunk rotation in children who come to the "Troniny" Scoliosis Treatment Centre Marek Kluszczynski, Anna Kluszczyńska, Jacek Wąsik, Marta Motow-Czyż, Adam Kluszczyński O10 Cobb angel measurement without X-ray, a novel method Ane Simony, Karen Hojmark Hansen; Hanne Thomsen; Mikkel Meyer Andersen; Morten Vuust O11 The postural tone magnitude and distribution in patients diagnosed with an adolescent idiopathic scoliosis: a preliminary study Irmina Blicharska, Jacek Durmała, Bartosz Wnuk, Małgorzata Matyja O12 From studies on the function of the respiratory system in children with body posture defects Andrzej Szopa, Małgorzata Domagalska-Szopa, Weronika Gallert-Kopyto, Tomasz Łosień, Ryszard Plintla O13 Scoliosis as the "first" sign of various diseases Franz Landauer, Karl Vanas O14 The effectiveness of core stabilization exercises versus conventional exercises in addition to brace wearing in patients with adolescent idiopathic acoliosis Gozde Gur, Necdet Sukru Altun, Yavuz Yakut O15 The effect of physiotherapy techniques on the body balance in patients with scoliosis treated with corrective appliances Piotr Gawda, Piotr Majcher O16 New combine method treating AIS – preliminary results Lior Neuhaus Sulam O17 Does a 4-week intensive course of ScolioGold therapy reduce angle of trunk rotation in scoliotic patients: a retrospective case series. Michael Bradley, David Glynn, Alex Hughes, Erika Maude, Christine Pilcher O18 Schroth physiotherapy method without bracing is an effective treatment for scoliosis in improving curves and avoiding surgery and should be offered as a treatment option for scoliosis in Canada: case series Andrea Lebel, Victoria Ashley Lebel, Judit Orbán O19 Rotation of the trunk and pelvis and coupled movements in the sagittal plane in double support stance in adolescent girls with idiopathic scoliosis Agnieszka Stępień, Krzysztof Graff O20 Curve progression analysis in Risser 0 patients orthotically managed with compliance monitors D. Speers O21 Conservative treatment in Scheuermann's kyphosis: comparison between lateral curve and variation of the vertebral geometry Angelo Gabriele Aulisa, Vincenzo Guzzanti, Giuseppe Mastantuoni, Andrea Poscia, Lorenzo Aulisa O22 The plaster cast in the conservative treatment of idiopathic scoliosis can still play a positive role? Angelo Gabriele Aulisa, Vincenzo Guzzanti, Francesco Falciglia, Andrea Poscia, Lorenzo Aulisa O23 Bracing for Adolescent Idiopathic Scoliosis (AIS) and Scheuermann Kyphosis : The issue of overtreatment in Greece Nikos Karavidas O24 Efficacy of Milwaukee brace for correction of scheurmann kyphosis Mohammadreza Etemadifar O25 The three dimensional analysis of the Sforzesco brace correction Sabrina Donzelli, Fabio Zaina, Monia Lusini, Salvatore Minnella, Luca Balzarini, Stefano Respizzi, Stefano Negrini O26 Quality of Life in adolescents with idiopathic scoliosis: A comparison measured by the Kidscreen 27 between scoliotic patients and healthy controls Kathrin Güttinger O27 The degree of illness acceptance in young women with idiopathic scoliosis treated with orthopedic braces: a preliminary study Jacek Durmała, Irmina Blicharska, Agnieszka Drosdzol–Cop, Violetta Skrzypulec–Plinta O28 Which are the personality traits of the patients with Adolescent Idiopathic Scoliosis? Elisabetta D'Agata, Judith Sánchez-Raya O29 How many Scolioses do exist in the same person? A zoom vision on the perception of the patient Judith Sánchez-Raya, Elisabetta D'Agata P1 The algorithm for the automatic detection of the pelvic obliquity based on analysis of the PA viev of the x-ray image Sławomir Paśko, Wojciech Glinkowski P2 Monitoring of spine curvatures and posture during pregnancy using surface topography – case study and method assessment Jakub Michoński, Katarzyna Walesiak, Anna Pakuła, Robert Sitnik, Wojciech Glinkowski P3 Spinal rotation under static and dynamic conditions: a prospective study comparing normative data vs. scoliosis Helmut Diers P4 The principle of non-surgical treatment of idiopathic scoliosis right-sided breast depending on the volatility of the formation of the intervertebral discs and vertebral bodies Piotr Majcher, Piotr Gawda P5 Unexpected late progression of adolescent idiopathic scoliosis treated with short-term, aggressive, full-time bracing and Schroth physiotherapy with excellent preliminary result: case study Andrea Lebel, Victoria Ashley Lebel P6 Visible posture in relation to the neuroanatomical and neurodynamical features in spinal deformations Piet van Loon, Ruud van Erve, Andre Grotenhuis P7 Immediate effects of scoliosis-specific corrective exercises on the Cobb angle after 1 week and after 1 year of practice Karina Zapata, Eric Parent, Dan Sucato P8 Retrospective analysis of idiopathic scoliosis medical records coming from one out-patient clinic for compatibility with Scoliosis Research Society criteria of brace treatment studies Krzysztof Korbel, Mateusz Kozinoga, Łukasz Stoliński, Tomasz Kotwicki P9 Adult female with severe progressive scoliosis possibly secondary to benign tumor removal at age 3 treated with scoliosis specific Schroth physiotherapy after refusing surgery: case study Andrea Lebel, Victoria Ashley Lebel P10 New aspects of scoliosis therapy planning and monitoring Helmut Diers P11 Outcome of intensive outpatient rehabilitation in an adult patient with M. Scheuermann evaluated by radiologic imaging – a case report Hagit Berdishevsky P12 The effectiveness of a Scoliosis Specific Home Exercise Program and bracing to reduce an idiopathic scoliosis curve with more than 90 % success in less than a year of exercises. Case report. Hagit Berdishevsky